Water resources management by conjunctive waters use, water harvesting and artificial recharge techniques - Bhamrah, P.J.S. (2003)
This article deals with water resources' (surface and groundwater) volumetric assessments and estimates their utilisation in irrigational and domestic needs. It is a fact that the fresh and potable water, although renewable, is very limited. There is growing shortage of usable water world over and it is going to be a major issue of the present country. Over exploitation of groundwater has created a very dangerous situation of declining water tables causing failures/drying of tube wells and deepening of abstractin structures leading to higher costs of pumping systems. The result studies of few projects undertaken and recommendations for saving and conservation of water have been elaborated. It discusses measure's to over come the water crisis by developing a strategy with water security including conservation, saving and management so as to chanellise water from where it is plentiful to places, where it is deficient and scarce. It emphasises that efficient water management should be the main thrust for economic development because our country has plenty of water resources. - Reproduced.
Keywords: Harvesting; Water resources management